(untitled) (Global Journal of Computer Science and Technology, 2013)
Cloud computing is the process of providing the virtualized services over the internet The space in the web commonly known as Cloud has been monitored by service provider In a real time scenario a user registers for a particular service and shares his data as well as access credential policies with CSP cloud service provider Though cloud computing has got major flexibility in data accessing users are very much concerned about their data security as it may be mislead by service providers They may share the owner s data to unauthenticated persons This is a big threat to the data owners In this paper a modern approach is proposed namely Cloud Information Accountability CIA framework and based on the notion of data liability We identify the common requirements and develop several guidelines to achieve data accountability in the cloud Once the data owner provides data the service provider will have full access and permission rights on the data Using traditional access control mechanisms after data rights are permitted the data is in the hands of the service provider We propose an algorithm which gives the details of people accessing the data using the automated logging details through the JAR files